Achieving 32.9% efficiency in Pb-Based quantum dot solar cells via SCAPS-1D simulation optimization - Md Hasnain; Abdul Wahed; Joyonta Das; Bassim Arkook; Moussab Harb; Nasim Mia (JPhys Energy)
This study presents a comprehensive investigation and in-depth analysis of the optimization of Pb-based quantum dot solar cells (QDSCs), concentrating on the influences of doping concentration, absorber layer thickness, defect density, temperature, and resistive elements. We systematically examined three absorber materials: lead sulfide (PbS), tetrabutylammonium iodide-treated PbS (PbS-TBAI), and lead selenide (PbSe) quantum dots (QDs). Optimal doping concentrations of $1 × 10^{17}$ cm ^−3 for PbS and $1 × 10^{22}$ cm ^−3 for both PbS-TBAI and PbSe were identified. Our findings reveal that precise control of these parameters can significantly enhance power conversion efficiency (PCE), achieving values of 24.6%, 28%, and 26.2% for PbS, PbS-TBAI, and PbSe, respectively. Additionally, we investigated the impact of absorber layer thickness on device performance. We discovered that a 1 µ m thickness for PbS yields a maximum PCE of 32.9% due to balanced photon absorption and reduced Shockley–Read–Hall recombination. Conversely, PbSe’s performance declined with increased thickness because of its layer-dependent bandgap. We found that lower defect densities ( $1 × 10^{14}$ cm ^−3 ) critically improve PCE and fill factor across all materials. The temperature-dependent studies demonstrated that PbS-TBAI exhibits remarkable resilience, maintaining efficiency under thermal stress due to effective surface passivation. Analyses of series and shunt resistances highlighted the importance of minimizing internal resistances to optimize device performance. The proposed device structure comprises a fluorine-doped tin oxide front contact layer, a silver sulfide (Ag _2 S) electron transport layer, the QD absorber layer (PbS, PbS-TBAI, or PbSe), and copper(I) oxide (Cu _2 O) hole transport layer. Utilizing cascade band alignment, we achieved a record PCE of 32.9%. This research highlights the significant potential of Pb-based QDSCs for achieving high efficiencies through promising material and structural optimization, positioning them as competitive candidates for next-generation solar technologies. The results provide a valuable understanding of designing high-performance QDSCs, paving the way for their integration into sustainable energy solutions.